Proof of the area–angular momentum–charge inequality for axisymmetric black holes - Gabach Clement, Maria Eugenia (2013)
We give a comprehensive discussion, including a detailed proof, of the area–angular momentum–charge inequality for axisymmetric black holes. We analyze the inequality from several viewpoints, in particular including aspects with a theoretical interest well beyond the Einstein–Maxwell theory.